If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(6k + -4) + 3k = -388 Reorder the terms: 7(-4 + 6k) + 3k = -388 (-4 * 7 + 6k * 7) + 3k = -388 (-28 + 42k) + 3k = -388 Combine like terms: 42k + 3k = 45k -28 + 45k = -388 Solving -28 + 45k = -388 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 45k = -388 + 28 Combine like terms: -28 + 28 = 0 0 + 45k = -388 + 28 45k = -388 + 28 Combine like terms: -388 + 28 = -360 45k = -360 Divide each side by '45'. k = -8 Simplifying k = -8
| 4x=5(3) | | 14x-16=124 | | 6v=4v+16 | | solvem-3.41=10.7 | | 4w=35-3w | | -4.1-9.12= | | 14u-49= | | 6(-8g+2)= | | -7v=-14 | | -4u=32 | | 7(5z-6)= | | 10(-6k-5)= | | 6(-2-5a)= | | x^2-6x+y^2+4y+13=9 | | 16y-7y=27 | | 4a+8a-3a= | | -2y+4=2(y+2) | | 64=4w+12 | | 3u-8=22 | | x(10x-2)=624 | | 5(x+3)=2x+18 | | 6=3j | | -7b-3b= | | 90+10x+5=180 | | 3x^3-6x(a-4)+12x^2-18x+24(a+5)= | | 1.50+0.60x=13.50 | | -1.5=-1.2 | | 12x^2-18x+24(a+5)= | | 6(2y-5)-3(5-3y)=10 | | 4(4x-3)-6x=4(2x-3)-24 | | (3-y)(3y+8)=0 | | 11=5+2n |